2017
DOI: 10.1371/journal.pgen.1006946
|View full text |Cite
|
Sign up to set email alerts
|

Plant microRNAs in larval food regulate honeybee caste development

Abstract: The major environmental determinants of honeybee caste development come from larval nutrients: royal jelly stimulates the differentiation of larvae into queens, whereas beebread leads to worker bee fate. However, these determinants are not fully characterized. Here we report that plant RNAs, particularly miRNAs, which are more enriched in beebread than in royal jelly, delay development and decrease body and ovary size in honeybees, thereby preventing larval differentiation into queens and inducing development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 58 publications
5
123
0
4
Order By: Relevance
“…The present knowledge on plant EVs is consistent with the idea of an EV-mediated effector shuttle in ckRNAi [1,22,[48][49][50][51][52][53][54][55]. Here, we tested the possibility that HIGS also involves vesicle transport of dsRNA-derived sRNAs.…”
Section: Exosome-like Vesicles From Leaf Extracts Of Cyp3rna-expressisupporting
confidence: 70%
“…The present knowledge on plant EVs is consistent with the idea of an EV-mediated effector shuttle in ckRNAi [1,22,[48][49][50][51][52][53][54][55]. Here, we tested the possibility that HIGS also involves vesicle transport of dsRNA-derived sRNAs.…”
Section: Exosome-like Vesicles From Leaf Extracts Of Cyp3rna-expressisupporting
confidence: 70%
“…However, the ability of bees to efficiently take up dietary small RNAs (e.g. miRNAs, siRNAs) is currently debatable [17,30,34,35]. While exchange of dietary RNA among adult bees can reasonably occur via trophallaxis [36], in our experiments, secretion of jelly that contained dsRNA-GFP required systemic distribution of the environmentally consumed dsRNA within the nurse bee.…”
Section: Discussionmentioning
confidence: 75%
“…These findings suggest a naturally occurring transmissible RNA pathway in honey bees. In line with this hypothesis, it has been reported that both worker and royal jellies contain small honey bee RNA populations, demonstrating endogenous bee RNA secretion into the larval diet [17,30]. To further explore the RNA repertoire in the jellies, including the natural occurrence of exogenous and pathogen-related RNA, we adapted a small RNA-seq protocol to sequence fulllength RNA up to 200nt (see materials and methods).…”
Section: Naturally Occurring Rna In Worker and Royal Jelliesmentioning
confidence: 90%
See 1 more Smart Citation
“…RNA exchange even occurs between the different domains of life: the bacterium Salmonella uses the host Argonaute to produce miRNA-like RNA fragments that increase its survival [16] , and mammalian miRNAs present in the gut can be internalized into bacteria and affect their growth thereby shaping the microbiota [17] . Although there has been more focus in the literature on RNA released from pathogens, RNAs are probably being exchanged between all sorts of other interacting species [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%